Morphological and morphometric analysis of cutaneous squamous cell carcinoma in patients with recessive dystrophic epidermolysis bullosa: a retrospective study. (15th May 2020) - Filoni, A.; Cicco, G.; Lospalluti, L.; Maglietta, A.; Foti, C.; Annichiarico, G.; Resta, L.; Bonamonte, D.
Abstract: Background: Recessive dystrophic epidermolysis bullosa is a highly disabling genodermatosis characterized by skin and mucosal fragility and blistering. Cutaneous squamous cell carcinoma (cSCC) is one of the most devastating complications, having a high morbidity and mortality rate. Patients with recessive dystrophic epidermolysis bullosa were reported to have up to a 70‐fold higher risk of developing cSCC than unaffected individuals. Immune cells play a role in cancer evolution. Objective: The aim of our study was to evaluate immunohistological differences between cSCC in patients with and without recessive dystrophic epidermolysis bullosa. Methods: A retrospective study of 25 consecutive cases was performed; five were biopsies of cSCC taken from five patients with recessive dystrophic epidermolysis bullosa; as controls we analysed 10 cSCC in subjects without recessive dystrophic epidermolysis bullosa (5 primitive, 3 postburns and 2 postradiotherapy), 5 cSCC in renal transplant recipients and 5 cutaneous pseudoepitheliomatous hyperplasia in patients with recessive dystrophic epidermolysis bullosa. Results: A significant reduction of CD3+, CD4+ and CD68+ between the cSCC in patients with recessive dystrophic epidermolysis bullosa compared to primary cSCC and a significant reduction of CD3+, CD4+, CD8+ and CD20+ were observed in cSCC in patients with recessive dystrophic epidermolysis bullosa compared to secondary cSCC. On the contrary, there was no difference in CD3+, CD8+, CD20+ and CD68+ expression when comparing cSCC in patients with recessive dystrophic epidermolysis bullosa to cSCC in renal transplant recipients. No significant difference was found in size, histopathology, grading, number of mitoses and EGFR expression between the different groups. Conclusions: Our data show a reduction in immune cell peritumoral infiltration. Considering the well‐known evolution of cSCC in patients with recessive dystrophic epidermolysis bullosa, as well as the younger age at diagnosis, it can be assumed that immune dysfunction might contribute to the cSCC aggressiveness in these patients.